2023
DOI: 10.7759/cureus.36545
|View full text |Cite
|
Sign up to set email alerts
|

A Severe Disc Herniation Mimics Spinal Tumor

Abstract: Lumbar disc herniation (LDH) is prevalent among adults aged 25-55 years who spend a considerable proportion of their time sitting or standing with heavy workloads. We report the case of a 33-year-old male waiter with severe LDH, causing compression of the nerve roots and spinal cord with neurological dysfunction, who presented to a chiropractic clinic. Magnetic resonance imaging (MRI) revealed a radiological differential diagnosis comprising LDH and an epidural mass lesion. To rule out serious pathology, a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Advanced imaging is essential for the early detection of abnormalities and diseases, allowing prompt intervention and treatment [8]. When substantial pain relief is not achieved with standard analgesics and conservative therapies, Hong Kong chiropractors often perform advanced imaging [9][10][11][12][13][14] to identify the defining features of spinal metastasis. The patient's MRI confirmed an infiltrative bone marrow process and pathologic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced imaging is essential for the early detection of abnormalities and diseases, allowing prompt intervention and treatment [8]. When substantial pain relief is not achieved with standard analgesics and conservative therapies, Hong Kong chiropractors often perform advanced imaging [9][10][11][12][13][14] to identify the defining features of spinal metastasis. The patient's MRI confirmed an infiltrative bone marrow process and pathologic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractors in Hong Kong utilize manual techniques such as spinal manipulation and soft tissue mobilization to address musculoskeletal dysfunction and reduce pain [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. According to a 2013 survey undertaken by the Census and Statistics Department of the Hong Kong Special Administrative Region, more than half (53.6%) of the 33,700 individuals who received chiropractic care had previously tried other forms of treatment.…”
Section: Chiropractic As An Effective and Low-risk Therapymentioning
confidence: 99%
“…[3] Chiropractors in Hong Kong are legally authorized to diagnose and treat musculoskeletal conditions. As conservative spine specialists and primary care practitioners, numerous studies have reported that chiropractors in Hong Kong provide non-invasive care for prevalent neuromusculoskeletal conditions and injuries [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, their inability to officially certify patients' incapacity limits the utility of chiropractic services.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar disc herniations are ubiquitous musculoskeletal conditions routinely encountered in chiropractic practice [1][2][3][4][5]. Although the pathophysiological mechanisms underlying nerve root compression and indications for surgical intervention are well established, the processes by which conservative modalities provide symptomatic relief and facilitate disc resorption remain unclear.…”
Section: Introductionmentioning
confidence: 99%